1993
DOI: 10.2307/416885
|View full text |Cite
|
Sign up to set email alerts
|

False Starts and Filler Syllables: Ways to Learn Grammatical Morphemes

Abstract: Studying the pragmatic microstructure of aphasic and normal speech: An experimental approach. L. Menn. In Menn & Bernstein Ratner (eds.), Methods for Studying Language Production. Hillsdale, NJ: Erlbaum. pp.377-401.(2000) In the beginning was the wug: Forty years of language elicitation studies. Ratner, Nan Bernstein & Lise Menn. 2000. In Menn & Bernstein Ratner (eds.), Methods for Studying Language Production. Hillsdale, NJ: Erlbaum. pp. 1-23. It's time to face a simple question: What makes canonical form sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
79
0
5

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(92 citation statements)
references
References 35 publications
7
79
0
5
Order By: Relevance
“…This variability, even though found in only one subject, could not be accounted for by rules at any linguistic level. Variability is, of course, a phenomenon found and accounted for by different researchers, such as Peters & Menn (1993) and López-Ornat (2003), but in our opinion it has not been sufficiently operationalized and quantified.…”
Section: Studies On the Acquisition Of The Determiner Category In Rommentioning
confidence: 89%
See 1 more Smart Citation
“…This variability, even though found in only one subject, could not be accounted for by rules at any linguistic level. Variability is, of course, a phenomenon found and accounted for by different researchers, such as Peters & Menn (1993) and López-Ornat (2003), but in our opinion it has not been sufficiently operationalized and quantified.…”
Section: Studies On the Acquisition Of The Determiner Category In Rommentioning
confidence: 89%
“…We consider the term ' proto-articles ' (Lleó, 1997(Lleó, , 2001) appropriate in order to describe them, as long as it does not imply any kind of system-wide syntactic category. These vN utterances, when neither their functions nor their forms are completely adjusted to the normative model, could be explained, as some authors have proposed, by alluding to phonological bootstrapping processes (Peters & Menn, 1993 ;Gerken, 1996 ;López-Ornat, 1997, 2003.…”
Section: Discussionmentioning
confidence: 99%
“…She reported the same desire to retain syllable number and position of stress and found these factors to be the first to be managed in language acquisition. Similarly, Peters & Menn (1993) Peters & Menn (1993) Peters (1977), Peters & Menn (1993), Stem & Stem (1928), Vihman (1981). As Annalena did not apply these strategies in all situations or for all words, they obviously served to provide her with provisional substitutes that enabled the child to take part in the 'language-game' when there was too much information to process at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…Peters & Menn (1993) indicated that a child's limited attention span in the face of too much information is often restrictive to language acquisition.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, D observes that children have different learning mechanisms (e.g. Peters, 1977;Nelson, 1981;Peters & Menn, 1993). They may learn "top-down" (holistically), where whole units of information are stored as wholes and children have to learn how to decompose them, or "bottom-up" (analytically), where children learn individual words and build up structure from there.…”
Section: Uniformitymentioning
confidence: 99%